Perusahaan Kosmetik Berbahan Dasar Rumput Laut di Tengah Wabah Covid-19 (PT Rumah Rumput Laut, Kabupaten Bogor) - Joko Ahadi Priyanto; Sugeng Heri Suseno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
PT Rumah Rumput Laut (RRL) is one company that produces cosmetic products from processed seaweed. Seaweed processing is one way to increase the industry's absorption of seaweed commodities which is still low in Indonesia, especially non-food products. The location of the company is in Bogor Regency. In the midst of a pandemic of the Covid-19 epidemic, cosmetic competition will continue. The purpose of this research is to describe the cosmetic products made from seaweed, knowing the quality and competitiveness of cosmetics made from seaweed in the market before and after the Covid-19 outbreak. Cosmetic products from PT Rumah Rumput Laut are divided into three categories, namely mask, cream, and pomade. Data collection method is done by interviewing the company manager. The company is still producing amid the Covid-19 outbreak. However, the amount of production and sales decreased amid this Covid-19 outbreak. This is done so that the brand and employee welfare are maintained. Keywords: Covid-19 Plague, seaweed souse, production and sale